Qualidade e segurança de prescrições de medicamentos no âmbito da atenção primária à saúde - Batista, Almária Mariz (2022)
Prescribing errors are one of the main patient safety issues in primary care and may be caused by weaknesses in clinical-pharmacological and/or medication prescription writing criteria, but there is a lack of validated instruments to assess the quality of the writing of this prescription. This study aimed to develop and validate an instrument to assess the quality of drug prescription writing in primary care and to evaluate the quality of this prescription using this validated instrument. Initially, a validation study was developed via four steps: 1) Validity analysis of each indicator (relevance, adequacy and criterion); 2) Reliability analysis via intra- and inter-evaluator agreement of each indicator; 3) Analysis of the usefulness of each indicator; 4) Construction and reliability analysis of a weighted composite indicator based on the effectiveness and safety scores of each indicator. Then, a cross-sectional observational study was carried out in a municipality in the Northeast of Brazil in which QualiPresc was applied to a representative sample of prescriptions prepared by physicians from all 24 family health teams in the municipality in January/2021. The compliance of the indicators and their 95% confidence intervals were estimated in aggregate and stratified by dispensing units and prescriber. This included 29 indicators, but only 13 were approved for reliability, reliability, and usefulness. 12 indicators were removed for validity (validity index <90%) and 4 for not being useful in the context of the study. Three composite weighted indicators were tested, but only one was approved for reliability and utility. The validated instrument contains 13 indicators and 1 composite weighted indicator. The mean prescription quality level on a scale of 0-100 was 60.2 (95%CI 57.8-62.6). As for the compliance of prescriptions, the best were administration frequency (98.9%), prescriber identification (98.9%) and pharmaceutical form (85.6%). On the other hand, allergy reporting (0.0%), patient's date of birth (1.7%), non-pharmacological recommendations (1.7%) and directions on the use of the drugs (25%) were the indicators. with a lower prevalence of compliance, contributing with 69% of the non-compliances found. The mean prescription quality level on a scale of 0-100 was 60.2 (95%CI 57.78-62.55). QualiPresc's validity, reliability and usefulness are evidenced for evaluating the quality of drugs prescriptions writing in the context of primary care. The level of quality of the prescriptions evaluated is medium, but priorities were identified that should be considered in future studies and interventions for the quality of prescriptions in primary care.